Geometric phases causing lifetime modifications of metastable states of hydrogen - Trappe, Martin-Isbjörn; Augenstein, Peter; DeKieviet, Maarten; Gasenzer, Thomas; Nachtmann, Otto (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2016)
Externally applied electromagnetic fields in general have an influence on the width ofatomic spectral lines. The decay rates of atomic states can also be affected by thegeometry of an applied field configuration giving rise to an imaginary geometric phase. Aspecific chiral electromagnetic field configuration is presented which geometricallymodifies the lifetimes of metastable states of hydrogen. We propose to extract therelevant observables in a realistic longitudinal atomic beam spin-echo apparatus whichallows the initial and final fluxes of the metastable atoms to be compared with each otherinterferometrically. A geometry-induced change in lifetimes at the 5%-level is found, an effect large enough tobe observed in an available experiment.
Gesehen am 27.05.2020